The new geography of remote jobs? Evidence from Europe - Özgüzel, Cem (OECD Regional Development Papers, 2023)
The COVID-19 pandemic has led to a dramatic acceleration in the diffusion of remote work. This paper contributes to understanding the phenomenon by offering the first systematic exploration of the uneven diffusion of remote jobs across Europe. Using a combination of rich individual micro-data from the European Union Labour Force Survey and regional-level characteristics, the analysis makes three contributions. First, it provides a systematic approach to measure remote work across 30 European countries. Second, it shows that cities and capital regions adapted faster to remote work than other areas of the continent. Third, it identifies and tests what factors are associated with telework uptake during the pandemic. Results show that the uneven diffusion of remote work is primarily explained by composition effects, i.e., because cities hosted more workers in occupations and sectors more amenable to working remotely